The Influence of Accounting Knowledge, Work Experience, and Organizational Structure on Internal Control and Its Impact on Company Performance - Natalia, Helfi; Wahdiat, Irwan Sutirman; Firasati, Aoliyah (Universitas Gorontalo, 2026)
This study aims to examine the effect of accounting knowledge, work experience, and organizational structure on internal control and its impact on company performance. The research applies a quantitative approach using survey data collected from employees in various organizations. Data analysis was conducted using Structural Equation Modeling (SEM) to test the proposed hypotheses and evaluate the relationships among variables. The findings reveal that accounting knowledge has a positive and significant effect on internal control effectiveness. Work experience also significantly contributes to the improvement of internal control implementation. In addition, organizational structure was found to positively support the effectiveness of internal control systems within organizations. Furthermore, effective internal control has a positive and significant impact on company performance. These findings indicate that competent human resources and a well-structured organizational system are important factors in strengthening internal control and improving organizational performance.